2004
DOI: 10.1063/1.1810209
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe force microscopy as a tool for characterizing chemical sensors

Abstract: We report on the use of Kelvin probe force microscopy in measuring the shift of the contact potential difference of micron-scale areas. The experimental results provide important information required for understanding and modeling the electrical characteristics of chemically sensitive field-effect transistors (ChemFETs). The temporal evolution in the shift of the contact potential difference of chemically sensitive monolayers of free-base porphyrin and zinc-porphyrin on exposure to pyridine gas was studied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…[53] KPFM measurements have also been performed on quantum dots, [54,55] quantum wells under illumination, [56] laser diodes, [57] nanotubes, [58,59] and chemically sensitive field-effect transistors. [60] This technique permitted the measurement of the size dependence of the work function for different nanostructures, such as multi-walled nanotubes, [61] and the charging behavior of dots. [55] One of the most promising applications of KPFM is indeed its use on working devices, where the effect of current or light passing through the device can be observed on different areas of the device.…”
Section: Kpfm Of Conventional Inorganic Materialsmentioning
confidence: 99%
“…[53] KPFM measurements have also been performed on quantum dots, [54,55] quantum wells under illumination, [56] laser diodes, [57] nanotubes, [58,59] and chemically sensitive field-effect transistors. [60] This technique permitted the measurement of the size dependence of the work function for different nanostructures, such as multi-walled nanotubes, [61] and the charging behavior of dots. [55] One of the most promising applications of KPFM is indeed its use on working devices, where the effect of current or light passing through the device can be observed on different areas of the device.…”
Section: Kpfm Of Conventional Inorganic Materialsmentioning
confidence: 99%
“…This fundamental parameter largely reflects electron activities and is directly related to chemical, physical, and mechanical properties of materials [2][3][4][5][6][7][8]. Recent studies have shown that EWF can be used as a sensitive parameter to characterize many surface properties of biomaterials.…”
mentioning
confidence: 99%
“…Addition of charge at the native oxide surface also lowers its surface work function (secondary gate work function ⌽ M2 ), and consequently, V FB2 decreases (by 0.2 eV). 25 However, due to the fact that the charge added to the molecular monolayer is expected to be essentially immobile (it only changes the dipole moment of the molecules), the contribution of the V FB2 term can be ignored in this analysis. The V g2-L term is relevant only when the device is exposed to liquid solutions and will be considered later in the discussion.…”
Section: Resultsmentioning
confidence: 99%